Algebraic Informatics 6th International Conference, CAI 2015, Stuttgart, Germany, September 1-4, 2015. Proceedings - Maletti, Andreas (Theoretical Computer Science and General Issues, 2015)
This book constitutes the refereed proceedings of the 6th International Conference on Algebraic Informatics, CAI 2015, held in Stuttgart, Germany, in September 2015. The 15 revised full papers presented were carefully reviewed and selected from 25 submissions. The papers cover topics such as data models and coding theory; fundamental aspects of cryptography and security; algebraic and stochastic models of computing; logic and program modelling.